2022
DOI: 10.1083/jcb.202112073
|View full text |Cite
|
Sign up to set email alerts
|

Impaired XK recycling for importing manganese underlies striatal vulnerability in Huntington's disease

Abstract: Mutant huntingtin, which causes Huntington’s disease (HD), is ubiquitously expressed but induces preferential loss of striatal neurons by unclear mechanisms. Rab11 dysfunction mediates homeostatic disturbance of HD neurons. Here, we report that Rab11 dysfunction also underscores the striatal vulnerability in HD. We profiled the proteome of Rab11-positive endosomes of HD-vulnerable striatal cells to look for protein(s) linking Rab11 dysfunction to striatal vulnerability in HD and found XK, which triggers the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 73 publications
0
4
0
Order By: Relevance
“…For example, Huntington's disease model mice exhibit decreased cell surface expression of channel proteins, which are essential for presynaptic neurotransmitter release [ 68 ]. Chhetri et al [ 19 ] recently reported that the expression of mutant huntingtin with long polyQ tracts (HTT Q111) interfered with the endosomal vesicular trafficking and cell surface expression of membrane-bound receptors and transporters [ 19 , 69 ]. These reports imply that alterations in vesicular trafficking in neurodegenerative disorders are caused by polyglutamine expansion.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Huntington's disease model mice exhibit decreased cell surface expression of channel proteins, which are essential for presynaptic neurotransmitter release [ 68 ]. Chhetri et al [ 19 ] recently reported that the expression of mutant huntingtin with long polyQ tracts (HTT Q111) interfered with the endosomal vesicular trafficking and cell surface expression of membrane-bound receptors and transporters [ 19 , 69 ]. These reports imply that alterations in vesicular trafficking in neurodegenerative disorders are caused by polyglutamine expansion.…”
Section: Discussionmentioning
confidence: 99%
“…We first investigated the expression and mutation profiles of 159 necroptosis-related genes in ccRCC patients in TCGA and found that 18 necroptosis-related genes play an important role in ccRCC. Some studies have shown that gene mutations play a guiding role in the occurrence of diseases such as cancer and the prognosis of cancer patients ( 42 45 ). Therefore, we explored the variation of 18 key necroptosis-related genes.…”
Section: Discussionmentioning
confidence: 99%
“…Immunolabeling was performed with floating brain sections with procedures as previously described ( 40, 95 ). Sections were removed from cryoprotectant solution and washed three times in PBS at room temperature.…”
Section: Methodsmentioning
confidence: 99%